Modeling Uremic Vasculopathy With Induced Pluripotent Stem Cell-Derived Endothelial Cells as a Drug Screening System - Jang, Hye Ryoun; Cho, Hyung Joon; Zhou, Yang; Shao, Ning-Yi; Lee, Kyungho; Le, Hoai Huong Thi; Jeon, Junseok; Lee, Jung Eun; Huh, Wooseong; Ong, Sang-Ging; Lee, Won Hee; Kim, Yoon-Goo (Frontiers in Cell and Developmental Biology, 2021)
Background: Cardiovascular complications are the leading cause of mortality in patients with chronic kidney disease (CKD). Uremic vasculopathy plays a crucial role in facilitating the progression of cardiovascular complications in advanced CKD. However, the improvement of conventional research methods could provide further insights into CKD. Objectives: In this study, we aimed to develop a novel model of uremic vasculopathy as a potential drug screening system. Methods and Results: The effects of uremic serum and different combinations of uremic toxins on induced pluripotent stem cell (iPSC)-derived endothelial cells (ECs) of a normal control and a CKD patient were investigated using several functional assays. We found that a mixture of uremic toxins composed of high urea, creatinine, uric acid, and indoxyl sulfate exerted deleterious effects on normal control iPSC-ECs that were comparable to uremic serum by increasing reactive oxygen species and apoptosis, as well as suppression of tube formation. Additional characterization revealed a potential involvement of dysregulated TGF-β signaling as treatment with either losartan or TGF-β inhibitors led to the attenuation of adverse effects induced by uremic toxins. Importantly, impaired wound healing potential seen in CKD patient-specific iPSC-ECs was rescued by treatment with losartan and TGF-β inhibitors. Conclusion: Our study demonstrated that simplified uremic toxin mixtures can simulate the uremic micromilieu reproducibly and CKD patient-specific iPSC-ECs can potentially recapitulate susceptibility to uremic vasculopathy. This novel model of uremic vasculopathy may provide a new research tool as a drug screening system.